Integrating parametric design and additive manufacturing knowledge in industrial design education. (2022) - Kandikjan, Tatjana; Djokikj, Jelena; Mircheski, Ile; Angeleska, Elena
Abstract: Additive Manufacturing (AM) technologies are present in almost any industry. For industrial designers, AM technologies are important for prototyping of new design concepts, and for their evaluation in short time and with less effort. Physical prototypes in industrial design often represent the outer shape, main modules and basic motions proposed with the designed concept. They are useful for better communication and acceptance of the design. Efficient prototyping can support creativity and experimentation in design. However, AM technologies also have limitations, meaning that there are manufacturing restrictions that the designer needs to know. Lack of knowledge on DfAM tools and techniques can be seen as one of the barriers for the further implementation of AM. By implementing DfAM in the Industrial Design Engineering curriculum, future designers can work confidently with AM and design products that fully exploit the possibilities of these technologies. DfAM is a way of thinking, a way of designing that the future designers and engineers need to obtain in the educational process. In this paper, we present the learning process that connects parametric modelling, DfAM and AM technologies through practical examples of product modelling and prototyping. The product models are redesigned and physically prototyped by the students, using a selected AM technology. More advanced examples are introduced through student projects that can stimulate creativity in development of design ideas, based on improved understanding of how the objects are manufactured, to get more advantage from using AM technologies.